HISTOPATHOLOGICAL STUDY OF CERVICAL LESIONS IN A TERTIARY HEALTH CARE CENTRE IN INDIA. - Lucky Sriwastwa; Sunil Kumar; C. P. Jaiswal; Ashish Ranjan; Sadaf (Student's Journal of Health Research, 2023)
Introduction: The cervix is the lower cylindrical part of the Uterus which projects into the vagina. The cervix despite being a small part, is home to numerous disease conditions, including both neoplastic and non-neoplastic ones. Important among these conditions are Inflammatory conditions like Chronic cervicitis along with premalignant and malignant conditions like CIN and SCC. Most cervical cancers are caused by HPV, an oncogenic virus. The main objective of our study is to analyze the histopathological spectrum of different types of cervical lesions, both neoplastic and non-neoplastic. Methodology: A retrospective study was done on 380 hysterectomy specimens and cervical biopsies that were submitted to the Department of Pathology, Nalanda Medical College and Hospital, Patna from May 2022 to July 2023. Detailed histopathological assessment of various lesions of the cervix was done, including both non-neoplastic as well as neoplastic.  Results: Out of 380 cases that were taken into consideration, 340 (89.5%) had non-neoplastic lesions, and 40 (10.5%) had neoplastic lesions. 241 cases (63.4%) were that of Chronic non-specific cervicitis. Other non-neoplastic lesions were Chronic papillary endocervicitis, endocervical polyps, squamous metaplasia, and nabothian cysts. Nearly 14 cases (3.7%) were that of CIN 1, 10 (2.6%) had CIN 2, 3 (0.8%) had CIN 3, and 11 (2.9%) had SCC. 43 years was the mean age of the women with preinvasive lesions. The mean age of patients with SCC was 49.2 years. Conclusion: Chronic non-specific cervicitis was the most common disease condition affecting the cervix, comprising 63.4% of total cases. Neoplasms comprised 10.5% of all cervical lesions. Accurate histopathological diagnosis may help in the reduction of complications caused by chronic cervicitis. The accurate and timely diagnosis of premalignant conditions by histopathology may help in preventing disease progression and avoiding more invasive surgeries thereby reducing morbidity and improving their quality of life.